Macro benthic fauna in relation to limnological variables in a migratory bird visiting lake at Jahangirnagar University, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The abundance of macro benthic organisms was observed from a migratory bird visiting lake in Jahangirnagar University, Savar for a period from July 2016 to June 2017. A total of 22 species belonging to three phyla (viz. Mollusca, Annelida and Arthropoda) and 14 families was recorded with maximum abundance in summer season and minimum in winter season. Molluscan population (37%) was dominant in benthos, followed by Annelida (31%) and Arthropoda (28%). Average values of water temperature, dissolved oxygen and water pH were within standard permissible ranges in the aquatic habitats of the country. Water and soil parameters were in suitable ranges for the growth and abundance of benthos. Correlation indicated that Mollusca and Annelida were closely dependent on water temperature, water pH, water depth, soil organic carbon and soil organic matters, whereas Arthropoda had less dependency on them. In the present study lower Shanon-Wiener diversity index (2.55-2.92) and low species richness (18-24) clearly demonstrated that the lake is moderately polluted.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 99-106